2009
DOI: 10.1093/europace/eup179
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Thebesian valve anatomy and coronary sinus ostium: implications for invasive electrophysiology procedures

Abstract: Our study shows that some form of Thebesian valve is present in the majority of hearts (>70%). Of these, a significant minority (16%) had a valve morphology (covering >75% of the ostium, a fibrous, fibromuscular, or muscular composition, and devoid of fenestrations) that makes them a 'potentially complicating' structure interfering with the cannulation of the CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 20 publications
4
67
0
1
Order By: Relevance
“…The presented data are in concordance with our results. All these studies confirm the significant variability in the presence and arrangement of the TV [3,4,6,7,[9][10][11][12]. This study is the first one of this kind carried out in our country on our population.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The presented data are in concordance with our results. All these studies confirm the significant variability in the presence and arrangement of the TV [3,4,6,7,[9][10][11][12]. This study is the first one of this kind carried out in our country on our population.…”
Section: Discussionsupporting
confidence: 81%
“…Mak et al [10] published the results from 75 autopsied human hearts (54 with organic heart disease), that confirmed a wide variety of TV patterns. The valve was present in 73% of examined hearts, and the most common shape was semicircular (65.4%).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The Thebesian valve has been identified in a significant number of hearts examined by various researchers [2,8]. In their study on 54 hearts obtained from patients with atherosclerosis, cardiomyopathy, left ventricular enlargement and endocarditis, Mak et al [11] observed the CS valve in 73% of specimens. Meanwhile, Pejkovic et al [15] identified the Thebesian valve in 80% of their sample.…”
Section: Discussionmentioning
confidence: 99%